2018
DOI: 10.1002/mdc3.12672
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, Impact, and Communication of “Off” Periods in Parkinson's Disease: A Scoping Review

Abstract: Background Off periods are a common and disabling symptom of Parkinson's disease. We reviewed published research on understanding, impact, and communication regarding off periods to identify issues warranting further research. Methods We performed a scoping review, searching MEDLINE, EMBASE, Cochrane Library, CINAHL, and PsycINFO from 2006 to January 2018 for studies examining the impact of, understanding of, or communication about off periods. Results Twenty‐six papers met eligibility criteria. Twenty‐three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In addition to their direct effect on wellbeing, GI dysfunction has been reported to dampen medication responses and trigger response fluctuations in PwP 52 . Such fluctuations result in temporary or premature re‐emergence of symptoms, commonly referred to as “OFF” periods, which themselves are strongly associated with reduced quality of life 53 . In the current study, PwP reported elevated nausea, vomiting, bloating or heartburn in the current study, all which are symptomatic presentations of delayed gastric emptying and increased colonic transit time.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to their direct effect on wellbeing, GI dysfunction has been reported to dampen medication responses and trigger response fluctuations in PwP 52 . Such fluctuations result in temporary or premature re‐emergence of symptoms, commonly referred to as “OFF” periods, which themselves are strongly associated with reduced quality of life 53 . In the current study, PwP reported elevated nausea, vomiting, bloating or heartburn in the current study, all which are symptomatic presentations of delayed gastric emptying and increased colonic transit time.…”
Section: Discussionmentioning
confidence: 49%
“…Investigators performed a preparatory systematic review which showed that (1) off periods are among the most troublesome symptoms to PwP, with a broad-ranging impact on patient and carepartner activities, (2) PwP and caregiver understanding of off periods is suboptimal, and (3) communication regarding off periods is largely unstudied [14]. Based on these results, investigators drafted semi-structured interview guides for PwP, carepartner, and physician interviews covering topics relating to experiences, barriers, and facilitators of communication to address literature gaps (S1 Interview guide).…”
Section: Methodsmentioning
confidence: 99%
“…They value a patient-physician relationship with mutual respect, trust, openness and adequate time [6]. A recent systematic review of communication about off periods, however, identified only one study on this topic [14]. In that study, less than half of PwP reported discussing troublesome symptoms at every appointment [15].…”
Section: Introductionmentioning
confidence: 99%
“…OFF periods are a temporary re-emergence of symptoms of PD that are often controlled or partially controlled by medication. OFF periods are associated with poorer health-related quality of life in PD (1). The combination and severity of these symptoms are unique for each person with Parkinson's disease (PwP) and include a broad spectrum of motor and non-motor symptoms (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…A scoping review (1) found that there is a paucity of published information regarding communication about OFF periods between PwP or carepartners and treating physicians. One study was identified that assessed communication about OFF periods: A survey of PwP and their carepartners found that less than half of the PwP indicated that they discuss troublesome wearing off symptoms at every appointment (11).…”
Section: Introductionmentioning
confidence: 99%